Seismicity, Velocity Structure and Tectonics of the Arabian Plate - Ghalib, Hafidh A. A.; Aleqabi, Ghassan I. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The deployment of the North Iraq Seismographic Network (NISN) and of the array KSIRS and the implementation of the virtual Middle East Seismographic Network (vMESN) produced a wealth of unprecedented data for use in studying the seismicity, velocity structure and some aspects of the tectonic activities associated with the Arabian plate dynamics. Recent studies using stationary Global Positioning System (GPS) stations in the region clearly show the northeast trending transitional and counterclockwise rotational motions of the plate. Most of the seismicity is occurring in the crust along the Zagros and Taurus mountain ranges and their foothills, along the Dead Sea transform fault and along the rift zones in the Red Sea and the Gulf of Aden. Earthquakes with magnitude greater than 5 mb are not frequent. Likewise, intermediate and deep earthquakes are uncommon in the region. The great majority of the earthquakes occur as a result of the continental collision between the Arabian plate and the Iranian and Turkish plateaus. Preliminary analysis of the earthquakes’ spatial distribution suggests likely alignment with the faults in the region. Moment tensor analysis of the larger events, carried out as part of the routine data processing, suggests their focal mechanisms vary from normal, reverse to strike-slip depending on the local stress pattern and the event’s location relative to the Zagros and Taurus suture zones. The three-dimensional crustal seismic velocity structure of the Arabian plate and surrounding regions estimated from the dispersion of Rayleigh surface waves reflects the impact of the overlying 5-10 km thick sedimentary column on the morphology of the crystalline basement, the Conrad and Moho discontinuities whose depths range from 20- 25 km and 40-50 km, respectively. The teleseismic P-wave receiver function analysis provided an independent verification of the velocity models beneath the various stations used in the study of the region. In summary, the resulting models show remarkable correlation between the distribution of shear velocities and the major physiographic and tectonic provinces of the Arabian plate, Turkish and Iranian plateaus. It also helped delineate the extent of the Red Sea rift and the roots of the Zagros and Taurus mountain ranges.
Keywords: Arabian PlateSeismicityVelocity StructureSource Mechanism